Gerenciamento de leitos no setor de urgência e emergência - Oliveira, Izabella Soares de (2019)
Introduction: The deployment of the Inner Core of Regulation in university hospitals is recent, and many are the challenges to the structuring of work processes. Therefore, in order to meet a demand for institutional improvements and advances in the management of hospital beds in the urgency and emergency sector in which the researcher is inserted, the implementation of Kanban, a tool of lean thinking, was instigated. This project is aligned with the research line of organization and evaluation of health care systems, and was developed in partnership with the team of regulation, urgency and emergency and management of the institution. Objectives: To develop flowcharts and protocols for the management of hospital beds in the urgency and emergency sector; to develop a software for monitoring the Kanban management tool. Method: Action-research, with a qualitative approach. The population was composed of the multiprofessional team from the health regulation and evaluation and the urgency and emergency sectors. The research was conducted in a large-sized university hospital located in southeastern Brazil, and data production occurred during the period from May 21, 2018 to May 31, 2019. Six seminars were conducted with lasting an average of one hour and ten minutes. The data obtained during the meetings were recorded, transcribed and analyzed by categorical content analysis of Bardin. The development of the software used the method of user-centered design, carrying out five meetings with the team of information technology and software followed the standards of the hospital to facilitate the deployment. Results/Products: Six products were developed: protocols of deployment and implementation of the Kanban tool, flowcharts of deployment and implementation of the Kanban tool, protocol for mapping the contents of the software Kanban and the software for monitoring the Kanban tool. The software “CuidarTech Kronos” is a novelty for the management of beds in the urgency and emergency sector using the Kanban methodology. Conclusion: This study has the potential to generate impact and be applied at national, regional and local level, because it systematically describes the steps and resources needed for the deployment and implementation of Kanban for management of beds in urgency and emergency. The protocols and software are relevant to the scientific and technological development, and contribute to direct the actions of the professionals, to act as backup in decisions and in the establishment of new work processes, aiming to improve the quality of patient care and direct it to the resource necessary. The deployment of the Kanban within the hospital does not have a standardized methodology. Therefore, this study at local level will serve as the basis for the expansion to other hospital sectors, in addition to being able to guide researches at national, regional and local level, according to this same model or performing the necessary adaptations as the institutional reality. The protocols and flowcharts were recorded and will be available on the intranet of the institution. After the tests, the software will be registered and deployed.